2021
DOI: 10.1073/pnas.2107107118
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis and cell ordering in confined bacterial biofilms

Abstract: Biofilms are aggregates of bacterial cells surrounded by an extracellular matrix. Much progress has been made in studying biofilm growth on solid substrates; however, little is known about the biophysical mechanisms underlying biofilm development in three-dimensional confined environments in which the biofilm-dwelling cells must push against and even damage the surrounding environment to proliferate. Here, combining single-cell imaging, mutagenesis, and rheological measurement, we reveal the key morphogenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 57 publications
0
63
1
Order By: Relevance
“…This growth-induced roughening is markedly different from that observed in Ref. [72], where much smaller bacterial colonies growing as inclusions in stiff, cross-linked bulk gels retained smooth surfaces. Moreover, while highly-branched shapes have been previously observed for colonies growing on planar 2D surfaces, they are thought to only arise when the underlying surface is depleted in nutrients, thereby generating stochasticity in the ability of cells to access nutrient [1420, 24, 25, 37]; in our case, however, the surrounding matrix is nutrient-replete.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…This growth-induced roughening is markedly different from that observed in Ref. [72], where much smaller bacterial colonies growing as inclusions in stiff, cross-linked bulk gels retained smooth surfaces. Moreover, while highly-branched shapes have been previously observed for colonies growing on planar 2D surfaces, they are thought to only arise when the underlying surface is depleted in nutrients, thereby generating stochasticity in the ability of cells to access nutrient [1420, 24, 25, 37]; in our case, however, the surrounding matrix is nutrient-replete.…”
Section: Resultscontrasting
confidence: 93%
“…For instance, external fluid flows are now known to trigger the formation of streamers that stem from an initially surface-attached colony [11, 71]. Under quiescent conditions, small (≲ 10s of cells across) biofilm colonies constrained in strongly-cross-linked bulk gels adopt internally-ordered structures as they grow and push outward [72], mediated by elastic stresses arising at the interface between the colony and its stiff environment. However, the behavior of larger bacterial colonies growing freely in quiescent 3D environments remains underexplored, despite the fact that they represent a fundamental building block of more complex natural colonies.…”
mentioning
confidence: 99%
“…Indeed, while studies of chemotaxis typically focus on the role of the external nutrient gradient in driving cellular migration, our work highlights the distinct and pivotal role played by the cellular chemotactic response function in regulating migration and large-scale population morphology more broadly. Our work therefore contributes a new factor to be considered in descriptions of morphogenesis, which thus far have focused on the role of other factors—such as differential forcing by signaling gradients, differential proliferation, intercellular mechanics, substrate interactions, and osmotic stresses ( McLennan et al, 2012 ; Fujikawa and Matsushita, 1989 ; Bonachela et al, 2011 ; Nadell et al, 2010 ; Farrell et al, 2013 ; Trinschek et al, 2018 ; Allen and Waclaw, 2019 ; Beroz et al, 2018 ; Fei et al, 2020 ; Yan et al, 2019 ; Yan et al, 2017 ; Copenhagen et al, 2020 ; Smith et al, 2017 ; Ghosh et al, 2015 ; Zhang et al, 2021 )—in regulating the overall morphology of cellular communities and active matter in general.…”
Section: Discussionmentioning
confidence: 99%
“…From these observations, they better predicted developmental dynamics and 3D structure emergence of biofilm through a better deciphering of cellular interactions. Complementarily, by integrating rheological measurements, single-cell imaging by spinning disc confocal microscopy, and modeling, Zhang et al [33] built a comprehensive view of V. cholerae biofilm development in confined environments using an agarose gel entrapment model. Thereby, they demonstrated that mechanical stress governs morphogenetic development and cell ordering in V. cholerae confined biofilms.…”
Section: Advances In Biofilm 3d Characterizationmentioning
confidence: 99%